Jawabanmu

2014-04-22T22:38:48+07:00
x^4 - 4x^3 + 7x^2 + ax + b  = x² + 2x + 14 (hasil bagi) sedangkan sisanya
         x² - 2x - 3                                        adalah (a + 34)x  +  (b + 42)
selanjutnya (a + 34)x  +  (b = 42) = 8x + 10
berarti          a + 34 = 8
                         a  = 8 - 34
                             = - 26
                   b + 42 = 10
                           b = 10 - 42
                             = - 32
Jadi a + b = (- 26) + (- 32)
               = - 58